Extending the allelic spectrum at noncoding risk loci of orofacial clefting. Issue 8 (3rd June 2021) - Thieme, Frederic; Henschel, Leonie; Hammond, Nigel L.; Ishorst, Nina; Hausen, Jonas; Adamson, Antony D.; Biedermann, Angelika; Bowes, John; Zieger, Hanna K.; Maj, Carlo; Kruse, Teresa; Buness, Andreas; et al.
Abstract: Genome‐wide association studies (GWAS) have generated unprecedented insights into the genetic etiology of orofacial clefting (OFC). The moderate effect sizes of associated noncoding risk variants and limited access to disease‐relevant tissue represent considerable challenges for biological interpretation of genetic findings. As rare variants with stronger effect sizes are likely to also contribute to OFC, an alternative approach to delineate pathogenic mechanisms is to identify private mutations and/or an increased burden of rare variants in associated regions. This report describes a framework for targeted resequencing at selected noncoding risk loci contributing to nonsyndromic cleft lip with/without cleft palate (nsCL/P), the most frequent OFC subtype. Based on GWAS data, we selected three risk loci and identified candidate regulatory regions (CRRs) through the integration of credible SNP information, epigenetic data from relevant cells/tissues, and conservation scores. The CRRs (total 57 kb) were resequenced in a multiethnic study population (1061 patients; 1591 controls), using single‐molecule molecular inversion probe technology. Combining evidence from in silico variant annotation, pedigree‐ and burden analyses, we identified 16 likely deleterious rare variants that represent new candidates for functional studies in nsCL/P. Our framework is scalable and represents a promising approach to the investigation of additional congenital malformations with multifactorial etiology.